Characteristics of Participants Enrolled in a Brief Motivational Enhancement for Smokers - Copeland, Amy L. (Frontiers in Psychiatry, 2016)
Daily smoking is associated with elevated blood pressure, CO toxicity, and impaired pulmonary lung functioning. The benefits of successful smoking cessation are readily apparent, given the health improvements associated with cessation, as well as the reduction of secondhand smoke to which nonsmoking coworkers and family members are exposed. Previous literature indicates that providing personalized information to smokers (versus general base rates) without engaging in confrontational pressure to quit smoking, leads to increased interest in quitting smoking and willingness to enter smoking cessation programs. The goal of this study was to examine the pre-treatment characteristics of the smokers entering a brief motivational enhancement intervention based on personally tailored health feedback. Participants (N = 28) were 88.2% Caucasian, 59% male, and were an average of 23.0 years of age. On average, they smoked 20.08 cigarettes per day (CPD), for a mean of 6.6 years, a mean Fagerström Test for Nicotine Dependence (FTND) score of 4.7, and obtained a mean breath carbon monoxide (CO) reading of 19.1 ppm. Smoking related adverse health outcomes were predictive of stages of change (SOC) motivation to quit smoking. Implication for cessation programs are discussed.